Hotel Chain’s Strategic Options to Penetrate the Romanian Market - Smaranda Cosma; Cristina Fleseriu; Marius Bota (Amfiteatru Economic)
The European hotel industry is dominated by small companies that own and operate a hotel. The rest of the market contains hotel chains. Most of the international hotel chains realized the potential of the market and that is why they intend to increase the number of hotels opened in Romania, but for the moment, only 3.5% belong to international hotel chains. The objectives of the study are identifying the level of attractiveness of Romania for international hotel chains, establishing the options of penetration chosen by them and the main influence factors upon the penetration on the market. The decision made by a hotel company to carry out its activity in a foreign country and the penetration strategy into the market can be motivated by many reasons. The study revealed that Romania ranks 24 out of 27 in terms of the opportunities of American international hotel chain that wants to enter the market. Analysing the 20 international hotel chains present on the Romanian market was found that the preferred penetration strategy is contract management. Research has indicated that the country of origin of the international hotel chain, chain size, the number of hotel stars belonging to a chain and the hotel establishment year has a statistically significant influence upon the strategy used to penetrate Romanian hotel market.